2022
DOI: 10.1161/hypertensionaha.121.18714
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Overweight Risk Trajectories During Childhood and Their Associations With Elevated Blood Pressure at Late Adolescence: a Retrospective Cohort Study

Abstract: Background: Overweight during childhood is significantly associated with higher risk of high blood pressure (HBP) in later life. However, recognition of critical intervention period is limited. We aimed to analyze the changes in overweight risk during school-age and its relationship with HBP. Methods: Seventeen thousand eight hundred sixteen school-aged children (53.9% boys) with a mean follow-up time of 8.2 years were involved. Children’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In this issue, Wang et al 7 conducted a longitudinal cohort study of 17 810 children (7 to 18 years of age) to identify trajectories of the overweight risk and their associations with the risk of HBP. All data were acquired during annual physical examinations taking place in elementary and high schools in the city of Zhongshan in China between 2005 and 2016.…”
mentioning
confidence: 99%
“…In this issue, Wang et al 7 conducted a longitudinal cohort study of 17 810 children (7 to 18 years of age) to identify trajectories of the overweight risk and their associations with the risk of HBP. All data were acquired during annual physical examinations taking place in elementary and high schools in the city of Zhongshan in China between 2005 and 2016.…”
mentioning
confidence: 99%
“…Previous studies of our team, on the basis of populationbased analysis, found that children who started overweight during pubertal height growth had higher risk of HBP at late adolescence, compared to those who remained overweight during school-age (13). In the present analysis with individualbased exploration, we confirmed the previous findings, and further found that returning from obese to overweight, as well as from overweight to normal weight, would both lead to decreased SBP and DBP were displayed as mean ± standard error; HBP was displayed as number (%).…”
Section: Discussionmentioning
confidence: 75%
“…Pooled cohort study found that greater obesity duration was associated with worse blood pressure outcomes in mid-adulthood (11). Retrospective cohort studies from China and the United States found that both children who maintained a high level of body mass index (BMI) and those who transit from non-obese to obese status during childhood and adolescence would experience elevated hypertension risk during follow-up (12)(13)(14). Population-based studies also found that the peak of hypertension and weight status transition both occurred around the age of growth spurt, (13,15) while pooled analysis found that the prevalence of hypertension peaked at 7.89% among those aged 14 years (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (7)(8)(9) have clearly indicated that the causes of obesity are multifactorial and complex. The incidence of obesity among school-age children cannot be explained based on the behavioural factors of students alone; rather, the environmental conditions surrounding students could also influence students' health-related behaviours (10)(11)(12) .…”
mentioning
confidence: 99%